The Dilemma of Food Sovereignty and Supply Gaps: A Socio-Economic Analysis of the Free Nutritious Meals Program and Its Impact on the Resilience of Local Farmers: Dilema Kedaulatan Pangan dan Kesenjangan Pasokan: Analisis Sosio-Ekonomi Program Makan Bergizi Gratis terhadap Ketahanan Peternak Lokal - Arif Rahman Azis; Woki Bilyaro; Muhammad Dani; Nurazizah Ramadhanti; Rizky Amrullah Chaniago; Akbar Abdurrahman Mahfudz; Muhammad Subhan Hamka; Muhammad Hakim (BPFP Universitas Bengkulu, 2026)
The Free Nutritious Meal Program (MBG), positioned as a